Outcome of assisted reproductive technology in women aged 40 years and older - Abbas Aflatoonian; Maryam Eftekhar; Farnaz Mohammadian; Fariba Yousefnejad (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Human fertility has been declined all over the world. Advanced women's age is one of the most important factors in determining the success of reproduction and ageing has negative impact on ART outcome and advanced female age decreases the chance of live birth rates achieved using ART, especially after 40 years of age. Objective: To evaluate ART outcomes regarding to pregnancy, abortion, cycle cancellation and live birth rates in women 40 years and older.Materials and Methods: A retrospective study was performed on three hundred-thirteen women undergoing ART cycles in the Madar Hospital in Yazd. Women with age ≥ 40 years who indicated for ART enrolled the study regardless of the infertility type or etiology. In this study, we used data from IVF or ICSI cycles using fresh embryo transfer. Follow up was performed in regard to pregnancy, abortion, cycle cancellation and live birth rates.Results: The mean age of women was 41.87±1.97 years. Chemical pregnancy rate was 8.6% (27/313) per cycle. Clinical pregnancy rate was 3.8% (12/313) per cycle. Spontaneous abortion was observed in 63% (17/27) of patients with positive pregnancy test. The overall cancellation rate was 23.3% per oocytes retrieval. The overall live birth rate per cycle for all women who initiated an ART cycle at age ≥40 years was 3.2% (10/313) that eight of those women were under 42 years old.Conclusion: Based on our results, we suggest that women with age 42 years and above should be advised to use other options, including oocyte donation or adoption